Evaluasi Hasil Belajar Problem Based Learning pada Mata Pelajaran Desain Multimedia Interaktif (Studi pada Siswa Jurusan Multimedia Kelas XII SMKN 12 Malang) - Tahmidya Kamila Putri Nicahya; Wibisono Sukmo Wardhono; Retno Indah Rokhmawati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
Problem Based Learning is a learning model where students are given problems related to the real world. From this problem students are directed to study and construct these problems based on the knowledge and experience they have learned before. This study aims to determine student learning outcomes in the subject of Interactive Multimedia Design using the Problem Based Learning model based on cognitive aspects in class XII students majoring in Multimedia at SMKN 12 Malang. This study used the Quasi Experiment method which was divided into two classes, namely the experimental class which was given treatment in the form of applying the Problem Based Learning model and the control class which was not given treatment. The results of this study indicate that the pretest and posttest values of the experimental class (M = -35.00, SE = 1.535) with the implementation of Problem Based Learning are higher than the pretest and posttest values of the control class (M = -19.33, SE = 0.67). The difference is significant with t = 6.199 and p = 0.001. Price Sig. (2-tailed) < 0.05. So it can be concluded that there is a significant difference that the pretest and posttest scores in the experimental class are better than the pretest and posttest scores in the control class.